Methodological Contributions to Educational Research on the Formation of Social Thought - Delfín Ortega-Sánchez; Carlos Pérez-González (MDPI AG, 2022)
The main purpose of social science education is the formation of social thought for the understanding of reality from its critical and creative dimensions and for the intervention and democratic participation of a responsible and committed citizenship; that is, the formation of citizens capable of living democratically with each other and of participating in the social, labor, cultural, and political life of their world, and trying to improve it [...]